2018
DOI: 10.1177/0300060518787644
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal malignant schwannoma in a child

Abstract: Retroperitoneal malignant schwannomas are extremely rare. Only a few cases have been reported, only one of which occurred in a child. We herein report a case of retroperitoneal malignant schwannoma in a 2-year-old boy who presented with a painless mass in the right lumbar region. The mass had gradually enlarged during a 1-year period, and it was about the size of the patient’s fist at the time of consultation. Whole-abdomen computed tomography revealed a space-occupying lesion in the retroperitoneum infiltrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
6
0
3
Order By: Relevance
“…In a recent report, Xu Hao et al 9 reported a successful removal of 16-cm retroperitoneal schwannoma in an elderly patient; however, the evidence of excessive bleeding was seen in this case. Similarly, in a recent report by Wang Yun et al, 10 a pediatric case of a painless schwannoma near the right lumbar region was presented; however, after successful removal of the tumor, one month later, recurrence was seen. A schwannoma can often be removed without associated deficits, and the nerve axons are not disrupted in the course of the procedure.…”
Section: Discussionmentioning
confidence: 63%
“…In a recent report, Xu Hao et al 9 reported a successful removal of 16-cm retroperitoneal schwannoma in an elderly patient; however, the evidence of excessive bleeding was seen in this case. Similarly, in a recent report by Wang Yun et al, 10 a pediatric case of a painless schwannoma near the right lumbar region was presented; however, after successful removal of the tumor, one month later, recurrence was seen. A schwannoma can often be removed without associated deficits, and the nerve axons are not disrupted in the course of the procedure.…”
Section: Discussionmentioning
confidence: 63%
“…Because of its insensitivity to radiation and chemotherapy, re-surgical resection is recommended for recurrent schwannoma ( 28 ). Malignant schwannomas have a poor prognosis and a high recurrence rate, so early diagnosis is important while emphasizing the necessity of close postoperative follow-up ( 29 ). We should know that regardless of the nature of the tumor, the difficulty of surgery is closely related to the size of the mass and adjacent adhesions, so the importance of early surgery is emphasized instead of only considering the surgical technique ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Учитывая тот факт, что в клинике продолжительность онкозаболевания составила около 1 года 8 месяцев, сопровождалось продолженным инфильтративным ростом неоплазии в костный мозг, развитием гематогенных метастазов в различные органы, плохо поддавалась хирургическому и химиотерапевтическому воздействию, можно полагать, что данное злокачественное новообразование имело высокоагрессивный потенциал, склонный к гематогенной диссеминации. Вероятно, данная опухоль могла возникнуть из шванномы [2,8], о чем указывают сведения из истории болезни.…”
Section: Discussionunclassified
“…В доступной нам современной отечественной и зарубежной литературе имеются немногочи-КЛИНИЧЕСКИЕ СЛУЧАИ / CLINICAL CASES сленные описания отдельных клинических наблюдений злокачественной опухоли оболочек периферического нерва параспинальной локализации, тем более при развитии метастатического каскада [4,5,7,8,10,15].…”
Section: Discussionunclassified
See 1 more Smart Citation